2017
DOI: 10.1007/s10068-017-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the sensory characteristics and drivers of liking for gochujang (Korean fermented chili pepper paste)

Abstract: The present study investigated the sensory characteristics of 31 types of gochujang, a Korean fermented chili paste, produced in various regions of Korea. Generic descriptive analysis was conducted to analyze the sensory properties of the samples. Among these, four samples were selected for consumer taste test based on their distinct sensory profiles. The drivers of liking for gochujang were identified when the samples were applied to four different food systems. Consumers (age range: 20's-60's) rated the acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Determination of sensory drivers of liking on any given food products were reported in many food categories, including mild Cheddar cheese (Drake, Gerard, & Drake, ), Greek yogurt (Desai, Shepard, & Drake, ), orange juice (Ku, Park, Kim, Kim, & Koo, ), spreadable cheeses with different fat contents (Bayarri, Marti, Carbonell, & Costell, ), gochujang (Korean fermented chili pepper paste; Kim, Go, Kim, & Chung, ), and Doenjang (Kim et al, ; M. J. Kim, Kwak, & Kim, ). In the case of Doenjang , Kim et al () identified the sensory drivers of liking of commercial Doenjang , which were sweet and MSG‐like tastes and salty taste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of sensory drivers of liking on any given food products were reported in many food categories, including mild Cheddar cheese (Drake, Gerard, & Drake, ), Greek yogurt (Desai, Shepard, & Drake, ), orange juice (Ku, Park, Kim, Kim, & Koo, ), spreadable cheeses with different fat contents (Bayarri, Marti, Carbonell, & Costell, ), gochujang (Korean fermented chili pepper paste; Kim, Go, Kim, & Chung, ), and Doenjang (Kim et al, ; M. J. Kim, Kwak, & Kim, ). In the case of Doenjang , Kim et al () identified the sensory drivers of liking of commercial Doenjang , which were sweet and MSG‐like tastes and salty taste.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar content in general provide sweet taste perception, therefore the sugar content can be a key quality parameter driving consumer acceptability. Also color was determined to be a key parameter for consumers to describe the typical sensory characteristics of traditional Doenjang (Kim et al, ; Kim & Lee, ), implying that consumers perception is highly influenced by the appearance attributes including color.…”
Section: Discussionmentioning
confidence: 99%
“…Gochujang (Korean chili paste) was evaluated by Kim et al [68], who reported the development of 34 attributes by 10 panelists for 31 different samples. Their aim was to investigate the characteristics of different Gochujang made by various producers and to determine any correlation with consumer age segments differing.…”
Section: Sensory Descriptive Analysismentioning
confidence: 99%
“…Gochujang products have also been evaluated for consumer acceptability and to better understand their acceptance. The sensory drivers of positive response in different age groups were investigated by Kim et al [68]. Hong et al [69] conducted cross-cultural consumer testing between Korea, China, and the U.S. to provide information on country-specific factors affecting consumer acceptance of Gochujang dressing with different ratios of each ingredient.…”
Section: Consumer Studiesmentioning
confidence: 99%